Emergence hemodynamic changes and postoperative outcomes in hypertensive patients receiving antihypertensive therapy undergoing general anesthesia: an observational study - Nahin Mahmud; Ahsan Habib Khan; Debabrata Banik; Nazmul Huda Naim; M. Fahad (International Journal of Research in Medical Sciences, 2026)
Background: Hypertensive patients undergoing general anesthesia often continue antihypertensive therapy through the perioperative period, yet whether the number of preoperative antihypertensive agents predicts the need for intraoperative anesthetic modulation or postoperative outcome remains unclear. This study aimed to characterise antihypertensive medication burden, anesthetic modulation requirement and postoperative adverse events in hypertensive patients undergoing general anesthesia. Methods: This prospective observational study enrolled 60 diagnosed hypertensive patients undergoing elective surgery at Bangladesh Medical University, Dhaka, over twelve months. Patients were grouped as normotensive, hypotensive or hypertensive according to intraoperative blood pressure deviation from baseline. Number of antihypertensive medications, frequency of anaesthetic modulation, systolic, diastolic and mean arterial pressures according to medication count and postoperative adverse events were recorded and analyzed using SPSS version 26.0. Results: Single-drug therapy was used by 63.3% of patients, two-drug combinations by 23.3% and three or more drugs by 13.4%. Hypotensive patients most often required two episodes of anesthetic modulation (50.0%), while hypertensive patients most often required three (63.0%). Blood pressure did not differ significantly by medication count at any time point (p>0.05). Postoperative nausea and vomiting occurred in 50% of hypertensive, 33.3% of hypotensive and 9.3% of normotensive patients (p=0.007) and coughing occurred only in hypertensive patients (25%, p=0.003). Conclusions: Antihypertensive medication count did not predict perioperative hemodynamic instability, whereas intraoperative blood pressure status was strongly associated with modulation requirement and postoperative adverse events.